Spasialisasi Kerentanan Sosial Ekonomi Terhadap Perkembangan Wilayah Pesisir Daerah Istimewa Yogyakarta - yusliana, (ReTII, 2022)
One of the benchmarks in regional development is how the level of vulnerability of a region is socially and economically. This research was conducted with the aim of knowing the level of socio-economic vulnerability in the coastal area of ​​DIY, namely knowing the distribution and level of economic vulnerability in the coastal area of ​​DIY which was then spatialized in the form of a map. The approach taken in this research is descriptive quantitative with analytical tools using GIS. The assessment method is also used as a first step in parameter assessment to determine the level of vulnerability. The results of the analysis show that the level of socio-economic vulnerability in the coastal area of ​​Yogyakarta is divided into 3 categories, namely high, medium, with a classification of four regional developments. Developed areas are those that are economically classified as low vulnerability and socially included in vulnerability are Tanjungsari District, Sanden District, Temon District, Kretek District, Wates District and Galur District, Panjatan District. Developing areas are areas with high economic vulnerability and low social vulnerability. Tepus and Panggang sub-districts. Furthermore, underdeveloped areas are areas with high economic vulnerability and high social vulnerability, namely in the Girisubo District. The developed but depressed areas are areas with low economic vulnerability and high social vulnerability, namely Purwosari District, Saptori District and Srandakan District